Workplace tobacco cessation program in India: A success story - Mishra, Gauravi A. (Medknow Publications, 2009)
CONTEXT: This paper describes the follow-up interventions and results of the work place tobacco cessation study. AIMS: To assess the tobacco quit rates among employees, through self report history, and validate it with rapid urine cotinine test; compare post-intervention KAP regarding tobacco consumption with the pre-intervention responses and assess the tobacco consumption pattern among contract employees and provide assistance to encourage quitting. SETTINGS AND DESIGN: This is a cohort study implemented in a chemical industry in rural Maharashtra, India. MATERIALS AND METHODS: All employees (104) were interviewed and screened for oral neoplasia. Active intervention in the form of awareness lectures, focus group discussions and if needed, pharmacotherapy was offered. Medical staff from the industrial medical unit and from a local referral hospital was trained. Awareness programs were arranged for the family members and contract employees. STATISTICAL ANALYSIS USED: Non-parametric statistical techniques and kappa. RESULTS: Forty eight per cent employees consumed tobacco. The tobacco quit rates increased with each follow-up intervention session and reached 40% at the end of one year. There was 96% agreement between self report tobacco history and results of rapid urine cotinine test. The post-intervention KAP showed considerable improvement over the pre-intervention KAP. 56% of contract employees used tobacco and 55% among them had oral pre-cancerous lesions. CONCLUSIONS: A positive atmosphere towards tobacco quitting and positive peer pressure assisting each other in tobacco cessation was remarkably noted on the entire industrial campus. A comprehensive model workplace tobacco cessation program has been established, which can be replicated elsewhere.